2012
DOI: 10.1016/j.kjms.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carvedilol on serum and tissue oxidative stress parameters in partial ureteral obstruction induced rat model

Abstract: Although the pathological mechanism underlying kidney damage is not completely understood, it has been reported that reactive oxygen species (ROS) formed during ureteral obstruction may play an important role in this process. Carvedilol has been used in a limited number of studies examining oxidative injury. The aim of this study was to investigate the effect of carvedilol on serum and tissue oxidative stress parameters in the partial unilateral ureteral obstruction (PUUO)-induced rat model. To our knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…As renal blood flow increases in the first 12 hour period after obstruction, hypoperfusion develops in advancing periods and is called secondary vascular injury. In current publications it is reported that ROS may lead to severe injury to the cell membrane by lipid peroxidation reactions and may have an important role in tubulointerstitial inflammation associated with obstructive nephropathy (3,4,14). Additionally, apoptosis has been reported to play an important role in pathophysiology of obstructive renal parenchymal injury (4).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As renal blood flow increases in the first 12 hour period after obstruction, hypoperfusion develops in advancing periods and is called secondary vascular injury. In current publications it is reported that ROS may lead to severe injury to the cell membrane by lipid peroxidation reactions and may have an important role in tubulointerstitial inflammation associated with obstructive nephropathy (3,4,14). Additionally, apoptosis has been reported to play an important role in pathophysiology of obstructive renal parenchymal injury (4).…”
Section: Discussionmentioning
confidence: 99%
“…Upper urinary tract obstruction is most often secondary to calculi, strictures, tumors and ureteropelvic junction or ureterovesical junction obstruction and is usually a reversible and partial unilateral condition (4). Although ureteral obstructions may cause kidney parenchymal damage due to several mechanisms, the exact pathophysiological mechanism of the changes in UPUO has not been fully understood (3,14). Intrarenal collecting system pressure elevation, renal blood flow impairment, vasoactive and inflammatory mediators are some of the known factors in pathophysiology of renal damage arising from UPUO (3, 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations